Decreased health‐related quality of life in children and adolescents with autoimmune hepatitis - Ana Beatriz Bozzini; Luciana Neder; Clovis A. Silva; Gilda Porta (Brazilian Society of Pediatrics, 2019)
Objective: The objective of this study was to evaluate the health‐related quality of life in children and adolescents with autoimmune hepatitis. Methods: A cross‐sectional assessment with the Pediatric Quality of Life Inventory 4.0 (PedsQL 4.0) was completed for 80 patients with autoimmune hepatitis and 45 healthy controls. Demographic data, prednisone dose, disease remission state, disease severity, and abdominal pain were also evaluated. Results: Based on the child self‐reports, physical, emotional, school, and total scores were significantly lower in autoimmune hepatitis patients when compared with controls (p < 0.05). Based on the parental reports, only the physical and total scores were significantly lower in autoimmune hepatitis patients versus controls (p < 0.05). Further analysis in autoimmune hepatitis patients with abdominal pain in the last month revealed significantly lower physical, social, and total median scores (p < 0.05). No differences were observed based on disease remission state or disease severity (p > 0.05). Autoimmune hepatitis patients who received a prednisone dose below 0.16 mg/kg/day at the time of the interview showed significantly higher physical scores than those who received a dose similar to or above 0.16 mg/kg/day (87.5 [50-100] vs. 75 [15.63-100], p = 0.006). Conclusions: Reduced scores in the physical, emotional, and school domains were observed in pediatric autoimmune hepatitis patients compared to control patients. Abdominal pain and corticosteroid dose negatively influenced the health‐related quality of life in children and adolescents with autoimmune hepatitis. Resumo: Objetivo: Avaliar a qualidade de vida relacionada à saúde em crianças e adolescentes com hepatite autoimune (HAI). Métodos: Foi concluída uma avaliação transversal com o Inventário Pediátrico de Qualidade de Vida 4.0 (PedsQL 4.0) para 80 pacientes com hepatite autoimune e 45 controles saudáveis. Os dados demográficos, a dose de prednisona, o estado de remissão da doença, a gravidade da doença e dor abdominal também foram avaliados. Resultados: Com base nos autorrelatos das crianças, os escores físico, emocional, escolar e total foram significativamente menores em pacientes com hepatite autoimune em comparação com os controles (p < 0,05). Com base nos relatos dos pais, apenas os escores físico e total foram significativamente menores em pacientes com hepatite autoimune em comparação com os controles (p < 0,05). Uma análise adicional em pacientes com hepatite autoimune com dor abdominal no mês passado revelou escores médios físico, social e total significativamente menores (p < 0,05). Nenhuma diferença foi observada com base no estado de remissão da doença ou na gravidade da doença (p > 0,05). Os pacientes com hepatite autoimune que receberam uma dose de prednisona abaixo de 0,16 mg/kg/dia no momento da entrevista mostraram escores físicos significativamente maiores que os que receberam uma dose semelhante ou acima de 0,16 mg/kg/dia [87,5 (50‐100) em comparação com 75 (15,63‐100), p = 0,006]. Conclusões: Escores reduzidos nos domínios físico, emocional e escolar foram observados em pacientes pediátricos com hepatite autoimune em comparação com pacientes do grupo de controle. Dor abdominal e dose de corticosteroide influenciaram negativamente a qualidade de vida relacionada à saúde em crianças e adolescentes com hepatite autoimune. Keywords: Quality of life, Autoimmune hepatitis, Childhood, Adolescence, Chronic disease, PedsQL 4.0, Palavras‐chave: Qualidade de vida, Hepatite autoimune, Infância, Adolescência, Doença crônica, PedsQL 4.0